2018
DOI: 10.2147/ijn.s156029
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of poly-L-lysine coating and heparan sulfate proteoglycan on magnetic nanoparticle uptake by tumor cells

Abstract: BackgroundPoly-l-lysine (PLL) enhances nanoparticle (NP) uptake, but the molecular mechanism remains unresolved. We asked whether PLL may interact with negatively charged glycoconjugates on the cell surface and facilitate uptake of magnetic NPs (MNPs) by tumor cells.MethodsPLL-coated MNPs (PLL-MNPs) with positive and negative ζ-potential were prepared and characterized. Confocal and transmission electron microscopy was used to analyze cellular internalization of MNPs. A colorimetric iron assay was used to quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 55 publications
2
24
0
Order By: Relevance
“…However, the application of a magnetic field exerted either no increase or a minor increase in the MNP cell value of the phenolic compound-modified nanoparticles in L-929 or LN-229 cells, suggesting that phenolic modification may facilitate uptake to a level near the maximum uptake capacity. Our results were consistent with previous findings indicating that the application of a magnetic field did not facilitate cellular uptake of the magnetic nanoparticles [3536].…”
Section: Resultssupporting
confidence: 93%
“…However, the application of a magnetic field exerted either no increase or a minor increase in the MNP cell value of the phenolic compound-modified nanoparticles in L-929 or LN-229 cells, suggesting that phenolic modification may facilitate uptake to a level near the maximum uptake capacity. Our results were consistent with previous findings indicating that the application of a magnetic field did not facilitate cellular uptake of the magnetic nanoparticles [3536].…”
Section: Resultssupporting
confidence: 93%
“…Human umbilical vein endothelial cells (HUVECs) were obtained with a protocol approved by the institutional review board of Chang Gung Memorial Hospital to study MNP-HUVEC interaction, as described previously 38,40. HUVEC were cultured in M199 medium with FBS (10%), heparin (100 μg/mL), endothelial cell growth supplement (ECGS) (30 μg/mL) and penicillin/streptomycin/amphotericin (1%) at pH 7.4.…”
Section: Methodsmentioning
confidence: 99%
“…Compelling evidence has suggested that sulfonated and carboxylated groups from many proteoglycans are targeted by CNPs and are closely implicated in their endocytosis ( Figure 2 A). In fact, due to their high negative charge, heparin/heparan sulfate proteoglycans, and to a lower extent, chondroitin sulfate B proteoglycans were shown to be major contributors for CNP endocytosis [ 103 , 104 ]. These proteoglycans commonly referred to as syndecans, tend to cluster upon multivalent binding of CNPs and associate with actin-binding proteins or F-actin to initiate endocytosis, which can proceed through clathrin-dependent and -independent mechanisms [ 105 ].…”
Section: Enhancing Ion Internalizationmentioning
confidence: 99%